Genetic diversity of Plasmodium vivax and Plasmodium falciparum field isolates from Honduras in the malaria elimination phase - Alejandro Zamora; Alejandra Pinto; Denis Escobar; Hugo O. Valdivia; Lesly Chaver; Gloria Ardón; Erick Carranza; Gustavo Fontecha (Current Research in Parasitology and Vector-Borne Diseases, 2025)
Malaria continues to be a major threat to public health in tropical regions, primarily affecting sub-Saharan Africa but also Asia, the Middle East, and Latin America. Malaria cases in Honduras have seen a significant decline and the country aims to eliminate the disease by 2030. This study examines the genetic diversity of Plasmodium falciparum and Plasmodium vivax in Honduras using four molecular markers (Pfama1, Pfglurp, Pvmsp3α, and Pvmsp3β), and the chloroquine resistance marker pfcrt in the context of the elimination phase. Our findings indicate that P. falciparum populations in Honduras are more homogeneous compared to P. vivax. The multilocus sequence typing (MLST) approach, using four loci from Pvmsp3α and Pvmsp3β, proved more effective in assessing the genetic diversity of P. vivax than individual marker analyses. No geographical clustering was observed for P. vivax haplotypes, either within Honduras or globally. In Honduras, P. falciparum appears to be under more effective control, while P. vivax presents a greater challenge due to its higher genetic diversity. This requires enhanced surveillance, targeted control strategies, and measures to prevent the reintroduction of variants. The isolates of P. falciparum also displayed a wild-type Pfcrt phenotype, suggesting susceptibility to chloroquine.